2020
DOI: 10.24203/ajbm.v8i4.6066
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Challenges to Electronic Human Resource Management (e-HRM) Adoption: A case of Small and Medium Enterprises (SMEs) in Tanzania.

Abstract: Most of the Small and Medium-sized Enterprises (SMEs) in the developing countries are yet to espouse and witness the full potential of electronic Human Resource Management (e-HRM) in their business operations despite its popularity in the developed countries. SMEs indispensable role in economic growth regarding employment creation and their contribution to GDP is globally acknowledged. A successful adoption of e-HRM may be the catalyst for the growth of Tanzania and many developing countries. Unfortunately, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Also, several researchers stated that e-HRM is becoming common and has the potential to provide amazing changes in organizations (Marler and Fisher, 2010;Kaur, 2013, Strohmeier andKabst, 2014;Nivlouei, 2014;Fındıklı and Bayarçelik 2015). Nevertheless, E-HRM is taken for granted as a driving force behind HRM value creation (Shah, Michael, and Chalu, 2020). This has created challenges in public sector organizations which this study aims to reveal.…”
Section: Introductionmentioning
confidence: 88%
“…Also, several researchers stated that e-HRM is becoming common and has the potential to provide amazing changes in organizations (Marler and Fisher, 2010;Kaur, 2013, Strohmeier andKabst, 2014;Nivlouei, 2014;Fındıklı and Bayarçelik 2015). Nevertheless, E-HRM is taken for granted as a driving force behind HRM value creation (Shah, Michael, and Chalu, 2020). This has created challenges in public sector organizations which this study aims to reveal.…”
Section: Introductionmentioning
confidence: 88%
“…Advantages include support from management and adherence to regulations. Risks include difficulties in conducting fair hiring practices and electronically complying with regulatory obligations, while barriers can include power clashes, privacy issues, and data protection issues [37].…”
Section: Conceptual Model For E-hrm Implementation In the Public Sect...mentioning
confidence: 99%
“…Many countries in Africa are experiencing challenges with e-HRM adoption. A Tanzanian study revealed that many organisations lacked resources to implement e-HRM systems, had limited knowledge and accessibility and connectivity challenges [48]. A study conducted in Ghana revealed that two-thirds of organisations had not implemented e-HRM, 39% of the respondents indicated that they were not ready to adopt e-HRM, while 53% of the respondents showed readiness to adopt e-HRM [49].…”
Section: Global E-hrm Adoptionmentioning
confidence: 99%